Judicial oversight of draft laws (Concept, importance and legal nature) (مجلة أبحاث قانونية, 2023)
Research Summary        Previous judicial oversight of draft laws in many countries falls within the jurisdiction of the constitutional judiciary, as it undertakes the task of examining the draft law before it is issued and enters into force. To ensure that it is free of defects that may mar its implementation in terms of the extent of its constitutionality in form and content, and the extent of its safety from legislative drafting defects. Oversight of the constitutionality of laws is affected by the vision of the legislator and the extent of his appreciation of their importance. Some countries have approved for the constitutional judiciary the authority to monitor draft laws, and this has been adopted. Direction of the French Constitutional Council in 2004. Considering that the principle of clarity of legislation is a constitutional principle, it imposes on the legislator the need to be careful and sufficiently precise and avoid ambiguous formulas that carry interpretation. With the aim of protecting the subjects of the law from any interpretation contrary to the Constitution
Keywords: draft laws; constitutional judiciary; constitutional legislator; previous oversight